Intra-Amygdala and Systemic Antagonism of NMDA Receptors Prevents the Reconsolidation of Drug-Associated Memory and Impairs Subsequently Both Novel and Previously Acquired Drug-Seeking Behaviors - Milton, Amy L. (J Neurosci, 2008)
The amygdala has long been considered a primary locus in mediating the effects of previously drug-associated stimuli on subsequent drug-seeking behavior, and the NMDA subtype of glutamate receptor within the amygdala is important for the consolidation of associations between environmental conditioned stimuli and the effects of addictive drugs. Here we demonstrate that amygdala NMDA receptors are also necessary for the reconsolidation of drug-associated memories. Using a behavioral task that specifically measures the conditioned reinforcing properties of a previously drug-paired stimulus, we show that infusion of the NMDA receptor antagonist d(-)-2-amino-5-phosphonopentanoic acid (d-APV) into the basolateral amygdala before a memory reactivation session disrupted the drug-associated memory and abolished subsequent instrumental responding for conditioned reinforcement. This effect was memory reactivation dependent, and the memory deficit persisted for at least 4 weeks. In contrast, infusion of d-APV immediately after the memory reactivation session had no effect on subsequent responding for conditioned reinforcement, indicating that NMDA receptors have a temporally limited role in the reconsolidation process. Furthermore, in molecular studies, we show that the reconsolidation-impairing effect of d-APV is correlated with downstream reductions in expression of the plasticity-related immediate early gene, zif268. We also demonstrate that systemic antagonism of NMDA receptors with MK-801 [(+)-5-methyl-10,11-dihydro-SH-dibenzo[a,d]cyclohepten-5,10-imine maleate] before memory reactivation subsequently reduced previously acquired instrumental drug-seeking behavior that depends on drug-associated cues acting as conditioned reinforcers. These data suggest that drugs modulating glutamatergic transmission at the NMDA receptor may be useful in the future treatment of relapse prevention in drug addiction through memory reconsolidation blockade.